Limitations and opportunities of using Hotmaps online heat atlas in heat energy planning : a case study of a Hungarian rural area - Csontos, Csaba; Harmat , Ádám; Campos, José; Munkácsy, Béla (International Journal of Sustainable Energy Planning and Management, 2025)
Rationalising the production and use of thermal energy would be the key to energy transition. However, in most rural areas heat planning and just transition is challenging. Energy geography solutions such as innovative online heat atlases, like Hotmaps are valuable tools for estimating household heat demand at municipality level. The aim of this study was twofold, firstly to validate the Hotmaps database with the help of field-obtained actual consumption data and to determine its usability for local thermal energy planning. Secondly to develop and test a complex methodology supporting the definition of a heating energy mix in a highly diverse landscape and energy mix in a Hungarian rural study area facing coal phase-out. The results confirmed that settlements with residential heat demand above 5,000 MWh/a could rely on the Hotmaps, however, mapping the local heating energy mix can only be done by field data collection, especially where the ratio of the solid fuels is over 50%. The heating energy mix can vastly vary even within a small geographical area which underlines the importance of in-situ rural energy mapping and makes clear the need to develop such complex but replicable methodologies as this paper has.